Climate Risk Management in Agricultural Extension in Kenya Curriculum - Grossi, Amanda; Dinku, Tufa; Hansen, James; Ruirie, Onesmus; Crane, Todd A. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Climate change and year-to-year climate variability have resulted in widespread impacts to ecosystems and people in Kenya, including increases in the intensity of weather extremes such as droughts and floods (Kogo et al., 2021). While these shifting and varying patterns have affected the productivity of many climate-sensitive sectors, Kenya’s agricultural sector which is largely rainfed has been especially impacted, adversely affecting the food security, nutrition, and livelihoods of millions of people (Gebre et al., 2023; Marigi, 2017).